Sclerosing mucoepidermoid carcinoma with eosinophilia of the salivary glands: Two additional cases not harboring MAML2 gene rearrangement - Hiroshi Harada; Masashi Takeda; Yohko Kohno; Shin-ichi Nakatsuka; Kenji Mishima; Akira Kurose (Elsevier, 2021)
Sclerosing mucoepidermoid carcinoma with eosinophilia (SMCE) is a rare subgroup of mucoepidermoid carcinoma characterized by dense stromal sclerosis and marked eosinophil infiltration. We herein describe two Japanese cases of SMCE. The patients were a 60 year-old female and a 67 year-old female, and each had a tumor of the parotid and upper lip, both of which were successfully removed with no signs of recurrence or metastasis. Histologically, the tumors consisted of round or polygonal, and partly spindle-shaped squamous cells with generally scant keratinization, which formed small and large invasive nests in the background of dense sclerotic stroma with marked eosinophil infiltration. Only a small number of mucus-producing cells and cytoplasmic mucin vacuoles were observed. The second case was unique in its presentation of melanin pigmentation, which is rarely found in oral tumors. Fluorescence in situ hybridization for MAML2 was performed, but no clear split signals were confirmed in either case. The histogenesis of SMCE, which is possibly different to that of ordinary mucoepidermoid carcinoma or the other counterpart of sclerosing mucoepidermoid carcinoma lacking eosinophilia, is further discussed comparing their genetic backgrounds. Their pathological features and diagnostic problems are also detailed.